SERANGGA PENGUNJUNG PADA KEBUN BENIH GENERASI KEDUA Melaleuca alternifolia (Maiden &Betchc) Cheel Di WEST WYALONG NEW SOUTH WALES AUSTRALIA - Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
It is important tu understand the floral visitor as preliminary study of aspecies in order to manage seed orchard. This study was aimed to observe the floral visitors and nectar nectar production of M. alternifolia flowers at second generation seeding seed orchard, West Wyalong, New Sounth Wales, Australia. One Five-minute count of insect visiations was carried out each morning between 10.00 and 11.00 am and each afternoon between 03.00 and 04.00 pm over five consecutive days during peak flowering. The numbersss of inflorescences for each sample branch, and all insect visits to each inflorescence, were recorded and collected. Insect traps were also placed on every sample tree to assist observation of the varieties of small insect. Insect traps were placed in the two partial exclusion treatments, i.e: (1) inside the fiberglass fly-screen with 2 mm apertures; (2) on the branch located in the middle of each tree without netting. Results revealed that flowers produced only a small amount of nectar which was indicated by a shiny appearance at the base of the floral cup in the morning, but this quckly disappeared as a result of evaporation. Thrips and flies and flies were dominat floral visitor of M. alternifolia, while several other types of insects, e.g. beetles, wasps, plant bugs, butteflies, predatory shield bugs and leafhopper were only infrequent visitors.